GATM, the human ortholog of the mouse imprinted Gatm gene, escapes genomic imprinting in placenta - Toshinobu Miyamoto; Kazuo Sengoku; Hiroaki Hayashi; Yoshihito Sasaki; Yoshihiro Jinno; Mutsuo Ishikawa (Genetics and Molecular Biology, 2005)
The GATM gene encodes L-arginine:glycine amidinotransferase, which catalyzes the conversion of L-arginine into guanidinoacetate, the rate-limiting step in the synthesis of creatine. Since, deficiencies in creatine synthesis and transport lead to certain forms of mental retardation in human, the human GATM gene appears to be involved in brain development. Recently it has been demonstrated that the mouse Gatm is expressed during development and is imprinted with maternal expression in the placenta and yolk sac, but not in embryonic tissues. We investigated the imprinting status of the human GATM by analyzing its expression in four human placentas. GATM was biallelically expressed, thus suggesting that this gene escapes genomic imprinting in placentas, differently from what has been reported in mouse extra-embryonic tissues.